Prevalence and clinical outcomes of nontuberculous mycobacteria in a Brazilian cystic fibrosis reference center - T.B. Aiello; Carlos Emílio Levy; Tânia Regina Zaccariotto; Ilma Aparecida Paschoal; Mônica Corso Pereira; Marcos Tadeu Nolasco da Silva; José Dirceu Ribeiro; Antônio Fernando Ribeiro; Adyléia Aparecida Dalbo Contrera Toro; Renan Marrichi Mauch (2018)
Nontuberculous mycobacteria (NTM) have been well established as an opportunistic pathogenic bacterial group for cystic fibrosis (CF) patients, with a prevalence ranging from 3% to 23% worldwide. A myriad of factors can bias the prevalence rate in different CF centers, especially misdiagnosis as systematic screening for NTM are still lacking in a number of centers. Here, we evaluated the presence and clinical outcomes of NTM isolation in microbiological respiratory cultures from CF patients attending a Brazilian reference center after setting up a systematic diagnostic protocol. Of 117 patients with respiratory samples cultured for NTM research, we found seven patients (6%) with at least one positive result for NTM [four males (57.1%), median age = 21 years (9-58)]. These cases are reported one-by-one. Median FEV1 was 40%, all patients showed signs of lung deterioration, with a median number of pulmonary exacerbations of three per patient/year. However, the impact of NTM isolation remains unclear in our center as all patients were coinfected with other CF respiratory pathogens. Our NTM prevalence assimilates to the lowest levels reported in literature, which is possibly influenced by the routinely applied Bacille Calmette-Guérin vaccine.